Dance Umbrella 2005 Mark Morris Dance Group - Simpson, Jane (Dance Books Ltd., Alton,Hampshire (UK), 2005)
Programme one reviewed. PALABRAS CLAVE: Mark Morris Dance Group.
Dentro del apartado "Dance Umbrella 2005".